Radical surgical resection of advanced thymoma and thymic carcinoma infiltrating the heart or great vessels with cardiopulmonary bypass support. Issue 1 (December 2015) - Ried, Michael; Neu, Reiner; Schalke, Berthold; von Süßkind-Schwendi, Marietta; Sziklavari, Zsolt; Hofmann, Hans-Stefan
Abstract Background Radical surgical resection of advanced thymic tumors invading either the heart or great vessels facing towards the heart is uncommonly performed because of the potential morbidity and mortality. To achieve a complete tumor resection, the use of cardiolpulmonary bypass (CPB) support might be necessary. Methods Retrospective analysis of the results in six patients, who underwent radical tumor resection with CBP support. Results Mean age was 46 years (27 to 66 years) and five patients were male. Tumor infiltration of the heart or the great vessels was evident in all patients. Five patients underwent induction therapy. Two patients were operated in complete cardioplegic arrest (antegrade cerebral perfusion:n  = 1). Arterial cannulation of the ascending aorta (n  = 5) or the femoral artery (n  = 1) and venous cannulation of the right atrium (n  = 4) or the femoral vein (n  = 2) were performed. Resection of the left brachiocephalic vein (n  = 6), resection of the superior caval vein (n  = 2), the ascending aorta (n  = 1) and the complete aortic arch with outgoing branches (n  = 1) were performed. A macroscopic complete resection (R0/R1) was achieved in five patients, whereas one patient was resected incompletely (R2). In-hospital mortality was 0 %. Three (50 %) patients needed operative revision (hematothorax:n  = 2, chylothorax:n  = 1). All patients had a complicated postoperative course and developed respiratory insufficiency. Conclusions Locally advanced thymoma/thymic carcinoma invading the heart or great vessels can be treated with radical surgical resection alongside with increased perioperative morbidity. The usage of CBP improves the chance of complete tumor resection in selected patients and might lead to a prolonged survival.